STRUCTURE OF POLICY EVOLUTION painting an integrated picture of change in policy and... institutional systems. - Bubak, Oldrich ([S.l.] : ROUTLEDGE, 2023)
This book advances novel tools for the study, analysis, and development of public policy, essential in a world of growing diversity, complexity, and accelerating change. Inspired by research in technology innovation, the book brings its forward applications into the studies of policy and institutional systems, answering, among others,the disciplinary need for a common model of change. Relating together the dynamics and the structure of policy evolution, the unified approach offers scholars important new insights into the logics and direction of policy development while advancing policy practitioners' capacity for forecasting and optimizing designs. Analyzing social and labour market policy development across two model jurisdictions, the United Kingdom and Denmark, it substantiates the new approach while demonstrating its significance to the study of welfare modernization and to policy scholarship more generally. The book will be of key interest to scholars and students of policy and institutional development, policy analysis, and public administration and management, as well as comparative policy, evolutionary and complexity policy, and social policy and welfare state modernization research.
OCLC-licensed vendor bibliographic record.
Keywords: Policy sciences; Welfare state; Labor policy -- Great Britain; Labor policy -- Denmark; Great Britain -- Social policy; Denmark -- Social policy; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Affairs & Administration